Penerapan Undang-Undang No. 32 Tahun 2009 Dalam Pengelolahan Limbah Cair di Usaha Dagang Tahu Jawa (Studi Kasus di Pabrik Tahu Usaha Dagang Jawa) - Muhammad Reza Novindri; Sri Hidayani; Elvi Zahara Lubis (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Tofu Industry Java Trading Business is an industrial factory engaged in food production that produces tofu. This industry was founded in 2009 which started with his two children who already had experience working in the tofu factory industry not far from their homes. This type of research is normative juridical namely the type of research conducted by studying written regulations so that this research is very closely related to the library. The results of the study are the level of danger from the liquid waste of tofu factory in the tofu trade business Java is not managed properly is damage to the quality of the environment, especially waters as one of the needs of humanity and other living things. Factors that caused the management of liquid waste did not go well according to Law number 32 of 2009, namely the ignorance of the entrepreneurs themselves, factors of education level, economic factors of entrepreneurs, government participation and law enforcement, factors of the role of the community and the role of the community in manage the environment. The legal consequences of these actions are written reprimands, government coercion, freezing of environmental permits, revocation of environmental permits.